2019
DOI: 10.1016/j.profnurs.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Nurse Faculty: Outcomes of a Three-Year Clinical Track Faculty Initiative

Abstract: Clinical track faculty often lack mentoring opportunities needed to develop their scholarship which may hinder their academic promotion. The Clinical Track Faculty Mentoring Initiative was designed to foster scholarship development and academic promotion of clinical assistant professors. Fifteen clinical assistant professors in two cohorts and their mentors participated in the Initiative. Each Cohort lasted two years with one overlapping year. Participating clinical assistant professors were required to attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This, therefore, highlights the need for mentors within the colleges. Some studies in other countries including the USA have found contrary findings and reported that a more formal strategy in the form of formal mentorship for NNEs within their colleges is a better strategy to facilitate the transition from practice to academia (Grassley & Lambe, 2015; Hinderer et al, 2016; Martin & Douglas, 2018; Shieh & Cullen, 2019). Therefore, we recommend that administrators of NTCs should create and implement faculty mentorship programmes to mentor NNEs.…”
Section: Discussionmentioning
confidence: 99%
“…This, therefore, highlights the need for mentors within the colleges. Some studies in other countries including the USA have found contrary findings and reported that a more formal strategy in the form of formal mentorship for NNEs within their colleges is a better strategy to facilitate the transition from practice to academia (Grassley & Lambe, 2015; Hinderer et al, 2016; Martin & Douglas, 2018; Shieh & Cullen, 2019). Therefore, we recommend that administrators of NTCs should create and implement faculty mentorship programmes to mentor NNEs.…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring of faculty by those more senior as a means to engage in scholarship is well established in the literature 3,4. Peer mentoring and coaching have also been shown to be effective in supporting faculty as they work to advance their program of research 5-8. Developing constructive and collegial relationships of mutual benefit can ease feelings of inadequacy as faculty transition from a clinical role into a scholarly career 9.…”
Section: Introductionmentioning
confidence: 99%
“…The transition of experienced nurse clinicians to the NNE role is receiving global attention as HTIs continue to rely on these nurse clinicians to take up faculty roles (Hoeksel et al, 2019 ). However, transitional support programmes and interventions are mostly in the developed countries (Nowell et al, 2017 ; Shieh & Cullen, 2019 ) with little emphasis placed on interventions required to ease the transition in Africa (Seekoe, 2016 ; Sodidi & Jardien‐Baboo, 2020 ). In the Ghanaian context, the situation is no different and often results in difficult and stressful transitions (Laari, Apiribu, Gazari, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of an integrative literature review on easing the transition from clinician to nurse educator revealed that formal preparation for teaching, guidance navigating the academic culture and a structured mentoring programme were key interventions that contributed to easing the transition (Grassley & Lambe, 2015). Whereas those studies did not focus on developing and implementing faculty transition interventions, the findings of other researches have underscored the urgent need to develop and implement faculty development, orientation and mentorship programmes aimed at easing the transition (Flanigan, 2016; Martin & Douglas, 2018; Owens, 2018; Shieh & Cullen, 2019).…”
Section: Introductionmentioning
confidence: 99%